Development of a Baja SAE off-road vehicle gearbox output shaft flange (Research, Society and Development, 2022)
The Baja SAE program was created by the Society of Automotive Engineers (SAE) in the United States with the aim of encouraging undergraduate students from schools worldwide to put into practice the academic concepts learned in order to develop the design, manufacture and assembly of an off-road vehicle to participate in the competition. Thus, the scope and main goal of this work was the development of the flange for coupling the gearbox output shaft to the driveshaft, which is an integral part of the powertrain system of this type of vehicle. Based on the project's input data, which includes the torque transmitted on the powertrain system's output shaft, and on the calculations developed after bibliographic research that was carried out, it was possible to define the minimum dimensions required for the flange. After this step, the dimensions were adjusted according to those of commercial machine elements used in the automotive market, such as CV joint and screws. Regarding the material for manufacturing the flange, it was selected the ductile cast iron ASTM A536 100-70-03 (GGG-70). For assembly the flange and CV joint, the cylindrical head Allen screw with internal hexagon and class 12.9 was selected, as it has good mechanical strength required for this type of application.